An evaluation of the quality of care for women with low risk pregnanacy: The use of evidence-based practice during labour and childbirth in four public hospitals in Tehran. Issue 11 (November 2015) - Pazandeh, Farzaneh; Huss, Reinhard; Hirst, Janet; House, Allan; Baghban, Alireza Akbarzadeh
Abstract: Objective: there is a consensus that the adoption of evidence-based practice contributes to the improvement of maternity care. Iranian National Guidelines for Normal Childbirth included evidence-based practice and were disseminated to hospitals in 2006 but little is known about the success of implementation. This study investigates the provision of care during labour and childbirth in comparison with national guidelines in four public hospitals in Tehran. Design: this was a descriptive evaluation study and investigated the provision of care during labour and childbirth using current evidence-based practice as the indicator of quality. Participants and setting: the observational and interview data were collected using checklist and interview guide based upon standards for evidence-based care in four public hospitals in Tehran. In 24 women who were admitted in normal labour, practices were observed until the end of the third stage of labour, to determine concordance with Iranian National Guidelines for Normal Childbirth. A further 100 postpartum woman were interviewed about their care during labour and childbirth in the early postpartum period before discharge from the postnatal ward. Findings: beneficial and lifesaving practices such as assessing mothers׳ well-being; removal of the placenta in the third stage of labour, as well as skin-to-skin contact and early initiating of breast feeding were recorded in most cases. However, the use of practices such as routine augmentation and induction of labour, fundal pressure, conducting routine episiotomy were noted. Key conclusions: this evaluation study shows good practice and areas for improvement as practices fail to meet evidence based standards. Thus, there is potential for quality improvement and economic savings in Tehran maternity hospitals. However closing the gap between guidelines based on best evidence and actual clinical practice in childbirth is a challenge. Practical solutions to enable implementation of evidence-based guidelines for normal childbirth in low risk women require further studies, especially from the providers׳ perspective. Implications for practice: national programs which focus on organisational framework, interventions to change provider׳s attitudes towards the development of a culture of birth as a normal and physiological process are more likely to be important in the Iranian context. Involving professional midwives more in the care for normal childbirth may help to improve quality of care during normal labour and childbirth in terms of evidence-based practice. Highlights: This study evaluated the provision of care during labour and childbirth employing the use of standards for evidence-based care. There were beneficial and lifesaving practices however the use of harmful practices were noted. The care during labour and childbirth partially followed evidence-based care.